Endodermal pouch-expressed dmrt2b is important for pharyngeal cartilage formation - Li, Linwei (Biol Open, 2018)
Pharyngeal pouches, a series of outpocketings derived from the foregut endoderm, are essential for craniofacial skeleton formation. However, the molecular mechanisms underlying endodermal pouch-regulated head cartilage development are not fully understood. In this study, we find that zebrafish dmrt2b, a gene encoding Doublesex- and Mab-3-related transcription factor, is specifically expressed in endodermal pouches and required for normal pharyngeal cartilage development. Loss of dmrt2b doesn't affect cranial neural crest (CNC) specification and migration, but leads to prechondrogenic condensation defects by reducing cxcl12b expression after CNC cell movement into the pharyngeal arches. Moreover, dmrt2b inactivation results in reduced proliferation and impaired differentiation of CNC cells. We also show that dmrt2b suppresses crossveinless 2 expression in endodermal pouches to maintain BMP/Smad signaling in the arches, thereby facilitating CNC cell proliferation and chondrogenic differentiation. This work provides insight into how transcription factors expressed in endodermal pouches regulate pharyngeal skeleton development through tissue–tissue interactions.